A comparison study of knowledge regarding pressure ulcer prevention among Nursing Students Of Health Campus, Universiti Sains Malaysia (USM) - Marasani, Halimah Tusadiah (Universiti Sains Malaysia, 2014)
Pressure ulcer has been recognized as a major cause of morbidity, mortality and a burden to healthcare (Whittington & Briones, 2004). The effects of pressure ulcer towards patients include physical, social, emotional, and mental (Spilsbury et al., 2007). Pressure ulcer needs considerable time for heal. Thus, it may disrupt patient quality of life during those times. This study aimed to determine the knowledge of pressure ulcer prevention among final year degree and diploma nursing student in Health Campus of Universiti Sains Malaysia (USM), Kubang Kerian, Kelantan and to compare their means knowledge scores. This is a cross-sectional study that was performed in a purposive sample of undergraduate final year nursing students include the degree and diploma nursing students. The students’ knowledge was assessed by using Pressure Ulcer Knowledge assessment Tool (PUKAT). Collection of data was performed between January to February 2014. The means knowledge of the score of degree students was 46.17(SD=11.29) and diploma students was 37.62(SD=10.06). Degree students had higher knowledge than diploma students regarding pressure ulcer. As conclusion, nursing students had low knowledge regarding pressure ulcer prevention. Thus, this lacking of knowledge should be highlighted in their education to improve it.